A invenção da imagem autoral de Chico Xavier: uma análise histórica sobre como o jovem desconhecido de Minas Gerais se transformou no médium espírita mais famoso do Brasil (1931-1938) - Cunha, André Victor Cavalcanti Seal da (2015)
The common thread throughout this research is an analysis of Chico Xavier as the carrier of an invented authorial image, built on the complex dynamics involving his representation as a psychographic writer in the production, receptivity and ownership of his works. We have approached Spiritism both as a cultural and editorial phenomenon. We have thus investigated the creation of an authorial image of Xavier, conceived as a collective construct from multiple individuals, including an intellectual elite linked to the Spiritism movement, as well as editors and readers. The chronological period of interest for this research ranges from the end of 1931 to the beginning of 1938. The analysis revealed that the literary work of Xavier was conceived according to the workings of the FEB, having flourished, from the end of the XIX century, within the internal power struggles among religious and scientific spiritualists, as well as within the disputes among different interlocutors in a time of criminalization by the first republican penal code. An overview of the spiritualist literature during the rising of Xavier allowed us to detect evidence of cultural bases for his psycographic writings. As far as his writings are concerned, we identified seductive and convincing strategies in the prefatory texts signed by the medium, involving the use of a large range of textual devices geared towards denying authorship. Yet another analytical movement was developed with a focus on the construction of the authorial image of the young medium from Minas Gerais, on the basis of the receptivity his works, of what was said about him by the first generation of his readers. We noted his rising in the spiritualist literature scenario, as part of a collective project, conceived and lead by frontrunners in the FEB. The editorial inner circle of the FEB, based on the criticism that attempted to disqualify the poetry book written mediunically, promoted transformations in the authorial image of Xavier in an effort to increase the authorship denial, in order to support the spiritual authenticity of the poems. Thus, the evidence of intellectual qualities of Xavier started to fade away. At the same time, his mediunic abilities showed a marked increase. Along with those, his virtuous behavior eventually granted him a reputation of an above-average medium. From such a remarkable position, Chico Xavier inserted different elements into the literary matrix of the current Spiritism of the FEB. This investigation allowed us to understand two strategies for the constitution of author-spirits. In Emmanuel, the editorial success of the character can be directly linked to his overflow that includes acting in paratextual and mostly paraliterary roles. This exercise was based on the fusion between representations of Emmanuel as both a spiritual author and as a guide to the medium. This position allowed the character to assume distinct roles, significantly increasing the possible courses of action of Xavier himself. In the peculiar case of Humberto de Campos, there was an appropriation of the already well-known literary character in order to transform him into an author-spirit. An effort was made to establish a continuous link between the conventional literary production of the chronicler from Maranhão and the psycographed production by Xavier. In this sense, we found, within the mediunic chronicles, the use of literary procedures that attempted to drain the authorial image from the literary to the psycographed text. Those bets turned out to be successful, allowing Chico Xavier to achieve a more prominent role as author-actor in the spiritualist literary scenario and within the setting of the large national press.